Evaluating the Acetylcholinesterase Inhibitory and Antioxidant Activities of Persea Americana Extracts - Dang, Kim Thu (H. : ĐHQGHN, 2019)
Medicinal plants are a potential source of enzyme acetylcholinesrerase (AChE) inhibitors, a key target in the treatment of Alzheimer’s disease. This paper studies the AChE inhibitory activity and the antioxidant effect of Persea Americana Mill extract. The sample leave, seed, exocarp and mesocarp of avocado were extracted with 50% ethanol and subsequently fractionated with n-hexane, ethyl acetate (EtOA) and n-butanol (n-BuOH) solvents. The AChE inhibitory activity was evaluated by Ellman’s colorimetric method and the antioxidant activity by screening DPPH free radicals. The results show that the seed of Persea Americana extract had the strongest AChE inhibitory activity and antioxidant effect, followed by the leave extract, and the exocarp extract and mesocarp extract were the weakest. The Persea Americana seed extract inhibited AChE activity in a dose-dependent manner with an IC50 value of 47.43 ± 0.5 μg/mL and the antioxidant effect with an IC50 value of 68.7 ± 0.35 µg/mL. The results also show that n–BuOH fraction of Persea Americana seed extract had strong AChE inhibitory and antioxidant activities with an IC50 value of 15.24 ± 0.52 µg/ml and 15.73 ± 0.42 μg/mL, respectively. The study results suggest that the Persea Americana Mill is a promising ingredient in Alzheimer’s disease prevention and treatment.